Sensitivity of Aeromonas obtained from poultry sources of Dhaka, Bangladesh - Alam, Saidul; Hassan, SMR; Shirin, Momena; Akond, Mohammad Ali (Bangladesh Journal of Botany, 2010)
About 30% poultry samples harboured Aeromonas spp. Sensitivity tests of 100 selected strains against 12 antibiotics revealed that 20 - 100% were resistant to nine and 18 - 85% were sensitive to eight antibiotics, respectively. All isolates showed multiple resistance to six to nine antibiotics and thus pose a risk for both chicken farms and public health. Key words: Aeromonas; Sensitivity; Resistant; Poultry sources; Bangladesh DOI: 10.3329/bjb.v39i1.5538 Bangladesh J. Bot. 39(1): 123-125, 2010 (June)